Studi Komparatif Kemampuan Komunikasi Matematis Menggunakan Model Pembelajaran Berbasis Proyek dan Model Pembelajaran Kooperatif Think Pair Share - Simanjuntak, Sinitta; Dasari, Dadan (Jurnal Padegogik, 2024)
Mathematics is an exact science that equips students with critical, strategic, creative, and analytical thinking skills so that mathematics needs to be given to students starting from elementary school. In learning mathematics, one of the learning objectives is to communicate ideas with symbols, tables, diagrams, or other media so that mathematical communication skills are needed to be possessed by students. The purpose of this study was to compare the mathematical communication skills taught using a project-based learning model and a Think Pair Share cooperative learning model. The sample of this study was class VIII-4 and VIII-9 at One of Medan's Junior High Schools, totaling 50 students. This study uses experimental research which shows the results of the research that the mathematical communication ability of project-based learning models has a higher average of 63.02 compared to mathematical communication skills using the Think Pair Share type of cooperative learning model which has an average of 52.13. The average value of the mathematical communication ability test obtained through giving the posttest at the end after being given treatment. So it is proven that the mathematical communication ability using project-based learning model is higher than the Think Pair Share type cooperative learning model.